Proceedings of the Proceedings of the 1st International Conference on Language and Language Teaching, ICLLT 2019, 12 October, M 2020
DOI: 10.4108/eai.12-10-2019.2292207
|View full text |Cite
|
Sign up to set email alerts
|

Need Analysis of English For Math Instructional Material

Abstract: Need analysis is the starting point in designing a course or developing material. It is used to gather information from the population about what they need in learning. This study aims at investigating the needs of English for math instructional material for the mathematics education department at UIN Alauddin Makassar. The design research was descriptive quantitative and qualitative research. The population of the research was 64 students, ten graduates, and two lecturers. Research data were collected by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…It is indicated that the students' goal in learning English is to be a professional worker when they graduate. This similar finding in (Nurpahmi et al, 2020). In his study found that students have fair ability in English skills, listening, speaking, reading and writing for support their career after graduating from university.…”
Section: Finding and Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It is indicated that the students' goal in learning English is to be a professional worker when they graduate. This similar finding in (Nurpahmi et al, 2020). In his study found that students have fair ability in English skills, listening, speaking, reading and writing for support their career after graduating from university.…”
Section: Finding and Discussionsupporting
confidence: 59%
“…So, Teaching English for biology subjects has started in junior high schools, especially in ninth grades in junior high schools in Germany which have implemented a bilingual program, maybe it will continue if the program also continues in college. According to Nurpahmi et al, (2020) stated English for Biology Education students is academic necessity which will later support their future, namely to get a scholarship and get a better job. This course emphasizes the basic skills that must be possessed by students including reading, writing, and speaking.…”
Section: English For Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…This process involves gathering information to design effective curricula and develop materials that meet specific educational requirements. According to numerous studies, a needs analysis is crucial for creating suitable course materials and activities, particularly in English for Specific Purposes (ESP) programs, where the focus is on teaching language skills tailored to specific fields (Irawan et al, 2018;Iswati, 2019;Misesani et al, 2020;Ria & Malik, 2020;Nurpahmi et al, 2020;Sari et al, 2022;Sundari et al, 2021). In light of this, the current research focuses on analyzing students' needs before developing English reading materials based on climate change, specifically descriptive texts.…”
Section: Introductionmentioning
confidence: 99%